Synthesis and emission properties of meso-substituted porphyrins - Tan, Ke Xin (Penerbit UTM Press, 2014)
Discovering of various organic dyes including porphyrins have attracted considerable attention to mimic the energy and electron transfer process for the artificial photosynthetic model systems which can be applied in developing optoelectronic devices. The accessibility on tailoring porphyrin properties makes them a good candidate to, be developed as the red light emitting materials for these applications. Thus, symmetrical and unsymmetrical molecular models of porphyrins with appended fluorenyl components and extended π electrons conjugated system were synthesized towards increasing the efficiency of energy and electron transfer. In the photophysical studies, the emission spectra proposed the evidence of energy transfer of appended fluorenyl arms into the porphyrin macrocyclic whereas the extension of conjugating system in porphyrins exhibits lower absorption energy and intensified the red fluorescent properties.